Cytomegalovirus events in high‐risk allogeneic hematopoietic‐cell transplantation patients who received letermovir prophylaxis. Issue 4 (5th May 2021) - Chen, Kaiwen; Arbona‐Haddad, Esther; Cheng, Matthew P.; McDonnell, Anne M.; Gooptu, Mahasweta; Orejas, Jose L.; Timblin, Kaitlyn; Silverman, Emily; Al‐Hamed, Rama; Soiffer, Robert J.; Hammond, Sarah P.; Marty, Francisco M.
Abstract: Letermovir is approved for the prevention of cytomegalovirus (CMV) reactivation and clinical disease in patients undergoing allogeneic hematopoietic‐cell transplantation (HCT). However, there is uncertainty about letermovir's ability to prevent clinical events during the period of prophylaxis as well as after the discontinuation of prophylaxis in the post‐transplant setting. We performed a retrospective cohort study in CMV‐seropositive allogeneic HCT recipients at high risk of CMV events, who received letermovir for primary prophylaxis from November 2017 through December 2019. We analyzed CMV outcomes for these patients during and after prophylaxis was discontinued. Patient outcomes were followed through June 2020. Sixty patients received letermovir for a median of 13 weeks (range, 1‐72 weeks). Thirteen (22%) patients had quantifiable CMV DNAemia (reactivation) during letermovir prophylaxis a median of 9 days (range, 1‐59 days) after starting letermovir. Five (8%) of these patients discontinued prophylaxis and received preemptive therapy (PET) with valganciclovir; eight (13%) continued letermovir as prophylaxis and CMV DNAemia resolved without PET. Thirteen patients (22%) had post‐prophylaxis CMV reactivation a median of 33 days (range, 14‐109 days) after letermovir discontinuation. In four (7%) of these patients, CMV DNAemia resolved without PET, and nine (15%) received PET. No patient developed CMV disease. Patients who developed CMV reactivation during prophylaxis did so shortly after initiation of letermovir, and most patients who developed CMV reactivation post‐prophylaxis did so within 60 days after discontinuation of letermovir. Letermovir prophylaxis has changed the presentation of CMV infection in high‐risk HCT patients.